2011
DOI: 10.5194/bg-8-1153-2011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of belowground carbon transfer assessed by in situ <sup>13</sup>CO<sub>2</sub> pulse labelling of trees

Abstract: Abstract. Soil CO 2 efflux is the main source of CO 2 from forest ecosystems and it is tightly coupled to the transfer of recent photosynthetic assimilates belowground and their metabolism in roots, mycorrhiza and rhizosphere microorganisms feeding on root-derived exudates. The objective of our study was to assess patterns of belowground carbon allocation among tree species and along seasons. Pure 13 CO 2 pulse labelling of the entire crown of three different tree species (beech, oak and pine) was carried out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 65 publications
2
49
1
1
Order By: Relevance
“…In certain studies, seasonal changes in belowground C allocation had no effect on the time lag between assimilation and use of assimilates in belowground respiration (Horwath et al, 1994;Högberg et al, 2010), suggesting that phloem path length and structural differences were the main determinants of C transfer velocity. In contrast, other studies reported considerable variation of the time lag during the growing season in the same trees Wingate et al 2010;Dannoura et al, 2011;Epron et al, 2011;Kuptz et al, 2011a) (Fig. 2).…”
Section: Plant-internal C Allocationmentioning
confidence: 70%
“…In certain studies, seasonal changes in belowground C allocation had no effect on the time lag between assimilation and use of assimilates in belowground respiration (Horwath et al, 1994;Högberg et al, 2010), suggesting that phloem path length and structural differences were the main determinants of C transfer velocity. In contrast, other studies reported considerable variation of the time lag during the growing season in the same trees Wingate et al 2010;Dannoura et al, 2011;Epron et al, 2011;Kuptz et al, 2011a) (Fig. 2).…”
Section: Plant-internal C Allocationmentioning
confidence: 70%
“…However, soil-respired CO 2 , which includes large contributions by root-respired CO 2 of unlabeled neighboring trees and heterotrophic soil respiration (Högberg et al, 2001;Andersen et al, 2005Andersen et al, , 2010, was reduced in δ 13 C by 1.5 to 3 ‰. Hence, beech fine roots and associated micro organisms appear to be a relatively strong sink for recently fixed C during summer (Högberg et al, 2001;Plain et al, 2009;Epron et al, 2011). Slightly pronounced shifts in soil-respired CO 2 under 2 × O 3 fit well with previously reported increases in fine-root turn-over of beech under long-term O 3 exposure (Nikolova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important to test hypotheses about temporal δ 13 C R patterns, for example, if δ 13 C R dynamics are heavily influenced by a sole component flux, resulting in a poorly mixed ecosystem source signal. Similarly, species-specific transport times of recent assimilates (Epron et al, 2011) can potentially delay the photosynthetic response signal in δ 13 C R , or abiotic phenomena (following section) can obscure component iso-fluxes (e.g. Ekblad et al, 2005;Knohl et al, 2005).…”
Section: Heterogeneous Flux Sourcesmentioning
confidence: 99%
“…Advances in our understanding of ecosystem processes through canopy labelling include assessing photosyntheticsoil-respiration coupling strength (Steinmann et al, 2004;Högberg et al, 2008;Bahn et al, 2009;Gamnitzer et al, 2009Gamnitzer et al, , 2011, carbon allocation patterns Epron et al, 2011), and shading impacts (Warren et al, 2012), to name a few. Quantitative methods of canopy labelling in connection with on-line tracer measurement techniques (Sect.…”
Section: Canopy Labellingmentioning
confidence: 99%
See 1 more Smart Citation